2011
DOI: 10.1007/7854_2011_123
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Experience may Positively Adjust the Trajectory of Senescence

Abstract: Although aging is inexorable, aging well is not. From the perspective of research in rats and complementary models, reproductive experience has significant effects; indeed, benefits, which include better-than-average cognitive skills, a slowing of the slope of decline, and a healthier brain and/or nervous system well later into life. Work from our lab and others has suggested that the events of pregnancy and parturition, collectively referred to as reproductive experience-an amalgam of hormone exposure, sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 160 publications
5
16
1
Order By: Relevance
“…Conversely, decreased fMRI activation in the prefrontal cortex is correlated with difficulties adjusting to parenthood (Laurent & Ablow, 2011;Swain et al, 2008). Neural changes in early motherhood are likely to have evolved to assist in the dual survival of parent and young (Kinsley, Franssen, & Meyer, 2011). Three recent studies have shown maternal cortical thickness changes in the prefrontal cortex across pregnancy and the early post-partum period (Hoekzema et al, 2017;Kim et al, 2018;Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, decreased fMRI activation in the prefrontal cortex is correlated with difficulties adjusting to parenthood (Laurent & Ablow, 2011;Swain et al, 2008). Neural changes in early motherhood are likely to have evolved to assist in the dual survival of parent and young (Kinsley, Franssen, & Meyer, 2011). Three recent studies have shown maternal cortical thickness changes in the prefrontal cortex across pregnancy and the early post-partum period (Hoekzema et al, 2017;Kim et al, 2018;Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, primiparous female rats during the late postpartum period outperform nulliparous females on spatial tasks despite comparable levels of cell proliferation and reduced cell survival (Kinsley et al, 1999; Darnaudery et al, 2007; Leuner et al, 2007; Pawluski and Galea, 2007; Hillerer et al, 2014). Studies examining spatial cognition in the post-weaning period have found that both primiparous and multiparous mothers exhibit enhanced spatial learning and memory compared to nulliparous rats even well into aging (Kinsley et al, 1999; Gatewood et al, 2005; Lemaire et al, 2006; Pawluski et al, 2006a; Pawluski et al, 2006b; Macbeth et al, 2008; Paris and Frye, 2008; Kinsley et al, 2012; Cost et al, 2014). But as in the late postpartum period, cell proliferation levels in primiparous rats are not significantly different than nulliparous rats (Leuner et al, 2007).…”
Section: Functional Consequences Of Altered Neurogenesis During Prmentioning
confidence: 99%
“…To this end, we also demonstrated higher growth factor expression and greater antioxidant defenses in naïve multiparous mice. Parabiosis of pregnant mice with nonpregnant female controls confers a regenerative benefit in virgin muscle, and emerging data suggest reproductive experience bestows lifelong benefits (20). Whereas nulliparous mice exhibited sharp reductions in systemic IL-4 and IL-10 concentrations, bFGF and VEGF concentrations remained relatively elevated in multiparous mice following stroke.…”
Section: Discussionmentioning
confidence: 99%